Ruthenium(II)-Catalyzed C–H Alkynylation of Heterocycles under Chelation Assistance - Liu, Yanping; Chang, Feng; Jiang, Qiaojuan; Ma, Zhiwei; Liu, Congjun (Synlett, 2018)
An efficient ruthenium(II)-catalyzed, chelation-assisted C–H alkynylation of heterocycles is described using hypervalent iodine–alkyne as an alkynylating reagent. This reaction proceeds smoothly under mild conditions with high regioselectivity and good functional group tolerance, delivering the desired alkynylated indoles, thiophene, furan, and pyrrole in high yields.
Keywords: ruthenium; alkynylation; hypervalent iodine–alkyne; chelation; heterocycles.